New inorganic binders containing ashes from agricultural wastes - Payá, Jordi; Monzó, José; Borrachero, Maria Victoria; Soriano, Lourdes; Akasaki, Jorge L. [UNESP]; Tashima, Mauro M. [UNESP] (Elsevier, 2017)
The using of wastes in the design of new binders for construction is the key for the success of new developments regarding environmental, technical, and economic issues. Biomass ashes usually contain reactive compounds for creating binding matrices by means of alkali activation and by blending with hydrated lime. These ashes are available in many countries, especially developing countries, and their using in new binders could be a feasible option for communities with few resources. Additionally, with the using of these biomass waste-derived ashes a reduction in the CO2 emissions from the preparation of the binder could be achieved. In this chapter, different uses of biomass ashes in the preparation of binders are described. Many examples have been reported, most of them involving the use of rice husk ash (RHA), sugarcane bagasse ash (SCBA), palm oil fuel ash (POFA), and wood ash (WA). In general, for alkali-activated systems, most reported results involve the use of mixtures of biomass ashes and other mineral admixtures (blast furnace slag (BFS), metakaolin, fly ash). Interestingly, the use of RHA as a component of the alkali activating solution shows excellent potential for replacing sodium silicate solution, which mitigates the economic and environmental issues associated with this chemical reagent. Hydrated lime-based binders containing biomass ashes were described and studied many years ago; however, in recent years this has become an active field in terms of new applications and new mixtures, because of the availability of biomass ashes and the interest in the design of low-CO2 binders.
Keywords: Alkali-activated cement; Biomass; Hydrated lime-based binder; Pozzolan